Problems of Teaching Arabic (Case Study in Private Universities in Banjarmasin)/(مشكلات تعليم اللغة العربية (دراسة الحالة في الجامعات الأهلية ببنجارماسين - Khairunnisa Khairunnisa (UIN ANTASARI, 2021)
This research is focused on the problems of learning Arabic (a case study at a private university) Banjarmasin and its solutions, the purpose of this research is to describe the implementation, to uncover the problems of learning Arabic, and to find out the efforts of teachers in overcoming the problems of learning Arabic. In this regard, the researchers asked questions to be answered in this study: how is the implementation of learning, how are the problems of learning Arabic, and how are the teacher's efforts in overcoming the problems of learning Arabic at the Islamic University of Borneo Muhammad Arsyad Al Banjari (UNISKA), Achmad Yani University, and the College of Teacher Training and Education (STKIP) PGRI Banjarmasin. The research approach used was descriptive qualitative method. Researchers used case studies to find out the problems of learning Arabic in learning activities. The data collection procedure was carried out by the researchers themselves by conducting observations, interviews, and documentation. Data analysis method: single site data analysis, then ended with multi-site data analysis intended as a process of comparing the findings obtained from each site and systematically presenting the results of similarities and differences. Based on the results of the analysis and discussion in this study, it can be concluded that the problems of learning Arabic that occur in the three private campuses are going well. The problems of learning Arabic at the three private campuses consist of linguistic and non-linguistic problems. And efforts to overcome the problems of learning Arabic by teachers using various learning media and learning strategies that are suitable for students. And foster enthusiasm and passion to be diligent in teaching.